2017
DOI: 10.2147/ott.s120662
|View full text |Cite
|
Sign up to set email alerts
|

Strategies of temozolomide in future glioblastoma treatment

Abstract: Glioblastoma multiforme (GBM) may be one of the most challenging brain tumors to treat, as patients generally do not live more than 2 years. This review aimed to give a timely review of potential future treatments for GBM by looking at the latest strategies, involving mainly the use of temozolomide (TMZ). Although these studies were carried out either in vitro or in rodents, the findings collectively suggested that we are moving toward developing a more efficacious therapy for GBM patients. Nanoparticles prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 43 publications
0
64
0
1
Order By: Relevance
“…TMZ is a DNA-alkylating compound, which is widely applied in treating malignant tumors, including glioblastomas, pituitary adenomas, and carcinomas (44,45). Combining chemosensitizers has been shown to profoundly improve the therapeutic effect of TMZ in different tumor models.…”
Section: Combination Of a Parp Inhibitor And Tmz Suppressed Sdhb-mutamentioning
confidence: 99%
“…TMZ is a DNA-alkylating compound, which is widely applied in treating malignant tumors, including glioblastomas, pituitary adenomas, and carcinomas (44,45). Combining chemosensitizers has been shown to profoundly improve the therapeutic effect of TMZ in different tumor models.…”
Section: Combination Of a Parp Inhibitor And Tmz Suppressed Sdhb-mutamentioning
confidence: 99%
“…The degradation rate of PLGA can be easily tailored from days to years by tuning the lactic to glycolic acid ratio, molecular weight, and the end cap groups and thus, providing versatility in the development of microparticles to deliver different drugs where the release kinetics need to be tailored to fit the drug of interest. Because of its versatility and biosafety, PLGA has been widely used for the fabrication of TMZ‐loaded particles for the treatment of glioblastoma . There are many different methods of producing PLGA microparticles including emulsion solvent extraction/evaporation, electrospraying, and microfabrication .…”
Section: Introductionmentioning
confidence: 99%
“…Because of its versatility and biosafety, PLGA has been widely used for the fabrication of TMZ-loaded particles for the treatment of glioblastoma. 21 There are many different methods of producing PLGA microparticles including emulsion solvent extraction/evaporation, 22 electrospraying, 23 and microfabrication. 24 Among the different fabrication methods, the emulsion solvent extraction/evaporation method is the most widely used method for the fabrication of drug-loaded microparticles as it is associated with an easy and low cost setup.…”
Section: Introductionmentioning
confidence: 99%
“…Resistance to chemotherapeutics is another difficulty for malignant gliomas treatment. As the most effective medicine for malignant gliomas, the cytotoxicity of TMZ induced glioma cells apoptosis and activated multiple signaling pathway increasing glioma cells damages [43][44][45] . It has been reported that TMZ promoted ROS production in glioma tissues [46][47][48] .…”
Section: Discussionmentioning
confidence: 99%